KORELASI ANTARA KEMAMPUAN BELAJAR MATEMATIKA DENGAN HASIL BELAJAR FISIKA SECARA ONLINE SISWA SMUN 1 TAKENGON - Richasanty Septima S; Yenni Tirtasari (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
This study aims to see and find out whether there is a relationship between the ability to learn mathematics and the results of learning physics online. Physics is a branch of science that studies the behavior of nature through experimental observations and quantitative measurements. In studying nature, Physics uses the language of mathematics to model natural phenomena in mathematical equations. In studying Physics, it is necessary to be able to The research method used is descriptive correlation analysis. The sample of this study was 60 students for three different classes. The research instrument is a report on student learning outcomes or a list of odd semester report cards for the 2020/2021 school year. The results of data analysis show that there is a significant relationship between mathematics learning ability and online physics learning outcomes with a large correlation coefficient (r) of 0.787 For class X-1, the value of the correlation coefficient is r = 0.734 for class X-2 and r = 0.661 For class X-3. This shows that if the ability to learn mathematics is high, the learning outcomes of physics will be high as well.